Cadmium, lead, and mercury mixtures interact with non-alcoholic fatty liver diseases. (15th September 2022) - Nguyen, Hai Duc; Kim, Min-Sun
Abstract: There is a scarcity of studies on the interactions between heavy metals and non-alcoholic fatty liver disease (NAFLD). Using a variety of statistical approaches, we investigated the impact of three common heavy metals on liver enzymes and NAFLD markers in a Korean adult population. We observed that cadmium, mercury, and lead all demonstrated positive correlations with liver enzymes and NAFLD indices. Our findings were mostly robust in secondary analysis, which included three novel mixture modeling approaches (WQS, qgcomp, and BKMR) as well as in silico investigation of molecular mechanisms (genes, miRNAs, biological processes, pathways, and illnesses). The 16 genes interacted with a mixture of heavy metals, which was linked to the development of NAFLD. Co-expression was discovered in nearly half of the interactions between the 18 NAFLD-linked genes. Key molecular pathways implicated in the pathogenesis of NAFLD generated by the heavy metal combination include activated oxidative stress, altered lipid metabolism, and increased cytokines and inflammatory response. Heavy metal exposure levels were related to liver enzymes and NAFLD indices, and cutoff criteria were revealed. More studies are needed to validate our findings and gain knowledge about the effects of chronic combined heavy metal exposure on adult and child liver function and the likelihood of developing NAFLD. To reduce the occurrence of NAFLD, early preventative and regulatory actions (half-yearly screening of workers at high-risk facilities; water filtration; avoiding excessive amounts of seafood, etc.) should be taken. Graphical abstract: Image 1 Highlights: Interactions between mixed metals and non-alcoholic fatty liver diseases (NAFLD) were found. Key genes related to mixed chemicals and NAFLD development were identified. Key molecular mechanisms affected by NAFLD-related combined metals were described. Metal' cutoff thresholds related to the risk of NAFLD were provided. miRNAs implicated in NAFLD development were reported.